“It hurt but it helped”: A mixed methods audit of the implementation of trauma- focused cognitive-behavioral therapy for psychosis - Hardy, Amy; Good, Sophie; Dix, Jayde; Longden, Eleanor (Frontiers in Psychiatry, 2022)
Background Emerging evidence supports the safety, acceptability, and efficacy of trauma therapies for people experiencing post-traumatic stress and psychosis, despite common concerns about iatrogenic harm when processing trauma memories for this population. However, to date there have been no mixed-method studies examining whether trauma-focused therapy can be implemented in routine care. This study reports an audit of a post-traumatic stress in psychosis clinic based in an inner-city trust in the U.K. National Health Service. Materials and methods People under the care of psychosis community mental health teams with a significant history of past trauma were referred to the clinic by their multidisciplinary clinicians. Referral outcomes were recorded, including the proportion of people for whom trauma-focused cognitive-behavior therapy for psychosis was indicated. Post-traumatic stress symptoms were assessed pre- and post-therapy for clinically significant change on the Post-traumatic Stress Checklist (version 4) and Post-traumatic Stress Checklist (version 5). A subgroup of service users was also interviewed about their experience of therapy, with transcripts analyzed using inductive thematic analysis. Results Seventy one service-users were referred to the clinic between 2014 and 2018, of which 51 (71.8%) attended an assessment. Of these, 20 (39.2%) were identified as having clinically significant PTSD symptoms with re-experiencing and were offered trauma-focused cognitive-behavior therapy for psychosis. Sixteen (80%) accepted and completed therapy, with no dropouts, and received a mean of 17.54 sessions (SD = 17.60, range = 12–91). There were no serious adverse events related to therapy. Clinically significant change was observed in 68.8% (n = 11) of the therapy group and post-therapy six people (37.5%) no longer met the threshold for clinically significant PTSD. Six service users completed an interview about their therapy experiences with findings organized within four main themes and associated subthemes: (1) Perseverance, (2) Establishing safety, (3) The challenges of therapy, and (4) Rebuilding one’s life after trauma. Conclusion Trauma-focused cognitive-behavior therapy for psychosis can be safe, acceptable, and effective when implemented in routine care. Lived experience perspectives highlight the emotional demands of therapy and long-term impact of trauma, thus underscoring the necessity of sufficient support and continuity of care both during and after therapy.